Evaluation of the Ex-situ Reproductive Capacity of Flemingia faginea (Guill.& Perr.) Baker, a Species of Medicinal Value in Burkina Faso - Gnoumou, Assan; Nana, Raymond; Daboué, Edith Marie Sylvie; Ouédraogo, Amadé (Journal of Agricultural Studies, 2021)
In Burkina Faso, medicinal plants are used mainly by the most vulnerable populations (70%). This study aims to promote the ex-situ reproduction of Flemingia faginea to make it accessible as a remedy for high blood pressure. Sexual reproduction of Flemingia faginea was carried out to evaluate the effect of 2 pre-germination treatments on the seeds’ germination rate. One pre-germination treatement included soaking seeds in tap water for 24h (T1), another soaking in boiling water until cooling for 24h (T2) while the control experiment did not have any pre-germination treatments (T0). We used seeds from two provenances: North-Sudanian (NS) and South-Sudanian (SS). The germination percentage and mean germination time (MGT) were calculated; additionally, the seedling height, diameter, leaves production were monitored for 2 months. The variance analyses fit to tukeys tests were used to compare the effects of the various treatments on germination rate, mean germination time and seedling growth. The best germination rate was obtained with T0 (96% NS and 79% SS). The best mean germination time (MGT) was 7.25 days T2. The best seedling growth was obtained with T0 and T1 (P=0.000). As the provenance is concerned, the NS provenance was the best source for germination capacity, for the best seedling growth. A test using seeds from NS combined at T0 conditions provides optimal conditions for production of F. faginea at almost no cost to the local population.